Inoculation of barley seeds with Azospirillum brasilense: shoot dry matter production and water use (Semiárida, 2020)
In semiarid and subhumid environments, plant growth promoting microorganisms mitigate abiotic stresses that frequently limit the grain production of winter cereals. Our objective was to quantify the field evolution of the shoot dry matter production of barley (Hordeum vulgare L.) cover crops inoculated with Azospirillum brasilense combined with two levels of fertilization. Four treatments combining a seed treatment with Azospirillum brasilense and nitrogen and phosphorus fertilization at sowing were placed in two sites from the semiarid and subhumid pampas region under contrasting initial water conditions. During the growing season, the water availability (rainfalls and water table contribution) was adequate for achieving normal growth of the crops. The fertilization and the inoculation treatments showed independent effects on the shoot biomass production with 23% mean response to inoculation and 44% mean response to fertilization. In the inoculated treatments, the greater shoot growth rate was observed between tillering and stem elongation anticipating the moment for maximum dry matter production compared with the treatments without inoculation. The inoculation of barley seeds with Azospirillum brasilense is a recommended management practice in dryland agricultural systems in the semiarid and subhumid pampas integrated with the production of annual summer crops.
Keywords: Dryland agriculture; cover crops; fertilization; biological promoters; sustainability